Method for optimising the performance of PML in anchor‐loss limited model via COMSOL. Issue 6 (23rd May 2022) - Li, Peng; Ou, Jun‐Yu; Yan, Jize
Abstract: Perfectly matched layer has been used for solving anchor‐loss limited quality factor in the Micro electromechanical systems. However, setting up a well‐behaved perfectly matched layer requires users to change the parameters of a perfectly matched layer to give correct results, while the current existing methods for choosing the right parameters are vague and lack theoretical support. Based on the mathematical theory of perfectly matched layer and simulation results of a beam structure's quality factor, this paper proposes a method for choosing the parameter to optimise the performance of perfectly matched layer in COMSOL. The accuracy of the proposed method is proved by matching the effect of substrate height on beam's quality factor with theory prediction. The author also studies the effect of beam height and beam width on the quality factor of the beam. The results demonstrate that simulated quality factors are in agreement with analytical values when the ratio of height over length is small but will show great divergence when height equals the length. This trend can be observed for the beam width as well. Especially for larger ratio of beam width over beam length, instead of decreasing monotonously as analytical equitation would expect, the simulated quality factor will converge into a stable value of 1700, which matches the result of two‐dimensional model for the same beam structure. This means that a three‐dimensional model has to be used for estimating the quality factor of a beam structure.